1987
DOI: 10.1177/036319908701200106
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Italian and Iberian Family History

Abstract: In the past decade a tremendous increase in family history research in Italy, Spain and Portugal provides new insight into family processes and has many implications for generalizations regarding the course of European family history. In this article many of these new findings are detailed and their historical and theoretical implications assessed. Previous generalizations regarding Mediterranean family history are examined in light of this new evidence. Among the topics discussed are the sources and methods e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…97 According to David Kertzer and Caroline Brettell, "The contrast with the northern regions of the peninsula, where women were a crucial part of the agricultural labor force, could not be more acute." 98 The Southern woman has been made out to have been subordinate to a regime of patriarchal authority and confined to the household. 99 Anthropologists in particular have used this kind of microdemographic information to help argue for cultural theories based around rigid sexual segregation and a "honor" and "shame" syndrome defining both sexuality and personal reputation.…”
Section: Wider Significance Of Findingsmentioning
confidence: 99%
“…97 According to David Kertzer and Caroline Brettell, "The contrast with the northern regions of the peninsula, where women were a crucial part of the agricultural labor force, could not be more acute." 98 The Southern woman has been made out to have been subordinate to a regime of patriarchal authority and confined to the household. 99 Anthropologists in particular have used this kind of microdemographic information to help argue for cultural theories based around rigid sexual segregation and a "honor" and "shame" syndrome defining both sexuality and personal reputation.…”
Section: Wider Significance Of Findingsmentioning
confidence: 99%
“…Later on, it became clear that the characteristics of these patterns, and especially of the Mediterranean one, are very fluid, and the typology put forward by Laslett is only a coarse generalization. This was highlighted by more recent studies in Portugal, Spain and Italy, which revealed great variability in these areas as far as household structure and marriage patterns are concerned (see for example Reher, 1990;Kertzer & Brettell, 1987). Nevertheless, Laslett's classification can still be used as a general framework and that is why it is mentioned here.…”
Section: Introductionmentioning
confidence: 93%
“…Como a política imigratória favorecia famílias, e os fazendeiros preferiam famílias maiores para os contratos de colonato (Stolcke, 1988:17), é provável que as famílias imigrantes nas regiões cafeicultoras fossem maiores, na média, que as famílias de brasileiros. A cultura italiana da época, sobretudo a dos camponeses da Itália setentrional, também valorizava a família conjunta, com irmãos casados morando e trabalhando junto, muitas vezes sob a supervisão do pai (Alvim, 1986:30;Durhan, 1966:30;Kertzer e Brettell, 1987;Pereira, 2002:185-189). Era relativamente comum os casais italianos emigrarem junto com irmãos, cunhados e pais, além dos filhos, uma tendência que aumentava o número de trabalhadores por família.…”
Section: Acesso à Propriedadeunclassified